Cervical Vertebral Osteophyte as a Rare Cause of Dysphagia: A Report of Three Cases - Yetim, T.D.; Karabacak, Y.B.; Bayaroğulari, H.; Taslak Şengül, A.T.; Üstün, N. (Baycinar Medical Publishing Unalan Mah., Unalan Cad., Bogazici Sitesi, 16. Blok, D:19, Uskudar,Istanbul 34700, 2015)
Diffuse idiopathic skeletal hyperostosis (ankylosing hyperostosis, Forestier's disease, spondylitis ossificans ligamentosa) is a chronic disease characterized by the widespread spinal osteofit formation due to enchondral ossification of paravertebral ligament and muscles. Treatment is primarily based on dietary changes and anti-inflammatory therapy in diffuse idiopathic skeletal hyperostosis patients suffering from dysphagia. Surgery should be considered in patients with a severe clinical status. In this article, we report three patients and discuss the diagnosis and treatment in the light of literature.
Nadir Disfaji Nedeni Olarak Servikal Vertebral Osteofit: Üç Olgu Sunumu
Keywords: Dysphagia; Idiopathic Skeletal Hyperostosis; Rare